Để M nguyên
=> 2n - 7 chia hết cho n - 5
=> 2n - 10 + 3 chia hết cho n - 5
=> 2(n - 5) + 3 chia hết cho n - 5
Vì 2(n - 5) chia hết cho n - 5
=> 3 chia hết cho n - 5
=> n - 5 thuộc Ư(3)
=> n - 5 thuộc {1; -1; 3; -3}
=> n thuộc {6; 4; 8; 2}
để M có giá trị nguyên \(\Rightarrow2n-7⋮n-5\) ( 1 )
ta có \(n-5⋮n-5\)
\(\Rightarrow2\left(n-5\right)⋮n-5\)
\(\Rightarrow2n-10⋮n-5\) ( 2 )
từ ( 1 ) và ( 2 ) \(\Rightarrow2n-7-\left(2n-10\right)⋮n-5\)
\(\Rightarrow2n-7-2n+10⋮n-5\)
\(\Rightarrow3⋮n-5\)
\(\Rightarrow n-5\in\text{Ư}_{\left(3\right)}=\text{ }\left\{1;-1;3;-3\right\}\)
lập bảng giá trị
\(n-5\) | \(1\) | \(-1\) | \(3\) | \(-3\) |
\(n\) | \(6\) | \(4\) | \(8\) | \(2\) |
vậy...................
M=\(\frac{2n-7}{n-5}\) =\(\frac{2n-10+3}{n-5}\) =2+\(\frac{3}{n-5}\) nguyên
\(\lrArr\) \(n-5\) là ước của 3,\(n-5=\pm3;\pm1\) hay \(n=\left\lbrace2;4;6;8\right\rbrace\)
\(\)\(\)\(\)
M=\(\frac{2n-7}{n-5}=\frac{2n-10+3}{n-5}=2+\frac{3}{n-5}nguyên\)
\(\lrArr n-5\) là ước của \(3\) \(,n-5=\pm3;\pm1\) hay \(n=\left\lbrace2;4;6;8\right\rbrace\) .\(\)